A new approach to research and theory development for financial firms-building a "house with windows". Issue 2 (10th April 2019) - Holland, John
Abstract : Purpose: The paper aims to rethink empirical models and theory used in explaining banks and financial institutions (FIs) and to enhance the process of theory construction. This is a provisional response to Colander et al. (2009) and Gendron and Smith-Lacroix's (2013) call for a new approach to developing theory for finance and FIs. Design/methodology/approach: An embryonic "behavioural theory of the financial firm" (BTFF) is outlined based on field research about banks and FI firms and relevant literature. The paper explores "conceptual connections" between BTFF and traditional finance theory ideas of financial intermediation. It does not seek to "integrate" finance theory and alternative theory in "meta theory" and has a more modest aim to improve theory content through "connections". Findings: The "conceptual connections" provide a means to develop ideas proposed by Scholtens and van Wensveen (2003) . They are part of a "house with windows" intended to provide systematic means to "take data from the outside world" whilst continuously recognising "the complexities of the context" (Keasey and Hudson, 2007 ) to both challenge and build the core ideas of FT. Research limitations/implications: The BTFF is a means to create "conversations" between academics, practitioners and regulators to aid theory construction. This can overcome the limitations of such an embryonic theory. Practical implications: The ideas developed create new opportunities to develop finance theory, propose changes in banks and FIs and suggest changes in the focus of regulation. Originality/value: Regulators can use the expanded conceptual framework to encourage theory development and to enhance accountability of banks and FIs to citizens.